Spurious peaks arising from multiple scattering events involving the sample environment in inelastic neutron scattering. (1st August 2014) - Pintschovius, Lothar; Reznik, Dmitry; Weber, Frank; Bourges, Philippe; Parshall, D.; Mittal, Ranjan; Chaplot, Samrath Lal; Heid, Rolf; Wolf, Thomas; Lamago, Daniel; Lynn, Jeffrey W.
Abstract : Well defined peaks with energies of about 18 meV have been observed in a variety of inelastic neutron scattering experiments on both single crystals and powders, using either the triple‐axis or the time‐of‐flight technique. They can easily be mistaken for signatures of real excitations. It has been found that they are due to multiple scattering events involving primarily the walls of the sample environment. Hence, they are particularly troublesome in experiments using very small samples, as have been used with recently developed high‐intensity neutron spectrometers. Measures required to reduce the unwanted scattering to a minimum are also discussed.